PENGARUH KAMPANYE #BYOT BRING YOUR OWN TUMBLER TERHADAP PERILAKU PEDULI LINGKUNGAN : Survei Pada Followers Instagram @starbucksindonesia - Ana Prima Larasati Nugraha, - (2019)
This research aims to know the magnitude of influence from #BYOT Bring Your Own Tumbler campaign on Instagram followers of @starbucksindonesia's environmental care behavior. The model used in this research is the Ostergaard campaign model. The research was conducted using a quantitative research approach. The research method used is the survey method. The population is Instagram followers of @starbucksindonesia with a sample of 100 respondents. The analysis technique for the effect of X variable on the Y variable using the coefficient of determination test. Data testing techniques were processed using the SPSS (Statistical Product and Service Solution) version 23. The results of this research indicate that the correlation of X variable with Y variable is strong. Based on the results of the calculation on the coefficient of determination, the results of the influence of X variable on variable Y is 45,5%. Thus result supported by the hipotesis signification test which Ho is rejected and Ha is accepted means that #BYOT Bring Your Own Tumbler campaign took effect on the greater the influence of information exchange about agriculture on Instagram followers of @starbucksindonesia's environmental care behavior